The main aspects of ademetionine administration in the early stages of the experiment in the correction of streptozotocin-induced diabetes mellitus with the characteristics of the presence and topography of lipid inclusions in the liver - Hrytsyshyn , L.M.; Popovych , Yu.I. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. The basis of the morphological changes of the liver in diabetes is the accumulation of fatty inclusions with the subsequent development of non-alcoholic fatty liver disease, which leads to insulin resistance. Hepatoprotective therapy allows these negative interrelated processes to be eliminated. Ademethionine (Heptral) is effective for such changes. Objective: to establish the main aspects of ademetionine administration after 14 and 28 days of the experiment with the assessment of the presence, possible dynamics and topography of fatty inclusions in the liver of rats with streptozotocin diabetes and its correction. Methods. 40 sexually mature male Wistar rats weighing 150-190 g were divided into 3 groups: I - 4 intact; II - includes 3 subgroups of 10 rats with simulated streptozotocin diabetes (with streptozotocin "Sigma", USA): 2A - without treatment; 2B – insulin correction from the 14th day; 2C - insulin and ademethionine were administered from the 14th day; III - 6 control. Results. In subgroup 2A, diffuse small vacuole lipid inclusions appear after 14 days. Topographically, they are most in zona intermedia (II) and peripherica (I). Zona centralis (ІІІ) is practicaly free. On the 28th day, a significant increase in the number of fat droplets is noted in subgroup 2A. There are massive small- and medium-caliber , sometimes of a showery nature in zones II and I. Zona ІІІ - small and isolated medium-caliber inclusions. There are significantly fewer inclusions in subgroup 2B; single small droplets, most in zone II. In subgroup 2C are practically no fatty inclusions. Conclusion. The optimal starting dose of ademetionine for the correction of decompensated diabetes is 4 mg/kg of body weight per day. It is not recommended 12 mg/kg. Maintenance - 8 mg/kg, in which the level of lipid inclusions corresponded to the norm.